THE THE INFLUENCE OF MANAGEMENT FUNCTIONS ON THE EFFECTIVENESS OF OIL PALM FARMERS' GROUPS IN TAPAK MERIAH VILLAGE, SILINDA DISTRICT, SERDANG BEDAGAI REGENCY: THE INFLUENCE OF MANAGEMENT FUNCTIONS ON THE EFFECTIVENESS OF OIL PALM FARMERS' GROUPS IN TAPAK MERIAH VILLAGE, SILINDA DISTRICT, SERDANG BEDAGAI REGENCY - Yuda Arya Pratama (RADJA PUBLIKA, 2026)
Farmer groups play an important role in increasing the productivity and success of smallholder oil palm farming. However, the effectiveness of farmer groups is greatly influenced by the implementation of management functions, including planning, organizing, implementing, and supervising. This study aims to analyze the influence of management functions on the effectiveness of the Sejahtera Farmer Group in Tapak Meriah Village, Silinda District, Serdang Bedagai Regency. The study used a quantitative approach with an explanatory research type. The study population consisted of 35 farmer group members, all of whom were sampled using a total sampling technique . Data were collected through observation, interviews, and questionnaires, then analyzed using multiple linear regression with the help of IBM SPSS. Before the analysis was carried out, the data had met the classical assumption test, which included normality, multicollinearity, and heteroscedasticity tests. The results showed that partially the variables of planning, organizing, implementing, and supervising had a positive and significant effect on the effectiveness of farmer groups with a significance value of 0.000 (p<0.05) each. Simultaneously, these four variables also significantly influence the effectiveness of farmer groups with an F-value of 29.806 and a significance level of 0.000. The coefficient of determination (R²) of 0.773 indicates that 77.3% of the variation in farmer group effectiveness can be explained by management functions, while the remaining 22.7% is influenced by other factors outside the research model. The results of the study indicate that planning is the variable that has the most dominant influence on farmer group effectiveness. Therefore, strengthening the implementation of integrated management functions is needed to increase the institutional effectiveness of oil palm farmer groups.